A nation betrayed - Gritz, Bo. ([s.l. : s.n.], 1988)
The video is a recording of Col. James'Bo' Gritz's talk on his findings about the CIA's drug trafficking with Burma, arms smuggling and political assassinations during President Reagan's administration.
'Additional fooage 1988'.
Keywords: United States Central Intelligence Agency; Drug traffic -- United States; Illegal arms transfers -- United States; Drug traffic -- Burma